2009
DOI: 10.1016/j.pain.2009.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Pain sensitivity can be assessed by self-rating: Development and validation of the Pain Sensitivity Questionnaire

Abstract: Experimental determination of pain sensitivity has received increasing attention because of emerging clinical applications (including prediction of postoperative pain and treatment response) and scientific implications (e.g. it has been proposed that above-average pain sensitivity is a risk factor for the development of chronic pain disorders). However, the use of experimental pain sensitivity assessment on a broad scale is hampered by its requirements on time, equipment and human resources and the fact that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

54
396
17
8

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 281 publications
(475 citation statements)
references
References 50 publications
54
396
17
8
Order By: Relevance
“…Pain Sensitivity Questionnaire (PSQ) and the Central Sensitivity Index (CSI), have been developed (Ruscheweyh et al, 2009;Mayer et al, 2012;Nijs et al, 2014) to assess various aspects of the clinical pain perceived. Significant correlations have been observed between PSQ scores and pain intensity Figure 1 A schematic illustration of how the different sensitisation processes may contribute to the assessed pain reaction (pain threshold).…”
Section: Clinical Assessment Of Central Sensitisationmentioning
confidence: 99%
See 1 more Smart Citation
“…Pain Sensitivity Questionnaire (PSQ) and the Central Sensitivity Index (CSI), have been developed (Ruscheweyh et al, 2009;Mayer et al, 2012;Nijs et al, 2014) to assess various aspects of the clinical pain perceived. Significant correlations have been observed between PSQ scores and pain intensity Figure 1 A schematic illustration of how the different sensitisation processes may contribute to the assessed pain reaction (pain threshold).…”
Section: Clinical Assessment Of Central Sensitisationmentioning
confidence: 99%
“…ratings (Ruscheweyh et al, 2009;Sellers et al, 2013) but possible associations to CS as assessed by experimental measures have not yet been established. The painDETECT questionnaire has been developed as a neuropathic screening tool for assessing neuropathic components in chronic musculoskeletal pain, such as chronic LBP (Freynhagen et al, 2006) and OA (Hochman et al, 2013), but it is not specifically useful for neuropathic pain conditions with sensory loss (Vollert et al, 2016).…”
Section: Clinical Assessment Of Central Sensitisationmentioning
confidence: 99%
“…This study has also shown that the subjective distress from physical symptoms is only weakly associated with levels of pain sensitivity, suggesting that the number of health complaints people will report is not simply due to individual biological factors involved in tolerance to discomfort (Ruscheweyh et al, 2009). As levels of perceived stress and anxiety were found to be associated with some but not all of the factors it is evident that individual psychological and environmental concepts can play a role in the perception of one's physical symptoms.…”
Section: Discussionmentioning
confidence: 67%
“…The pain sensitivity questionnaire (PSQ; Ruscheweyh et al, 2009) was used to assess pain tolerance. The PSQ comprises 17 items (3 of which are filler items) and each item describes a situation in which one may feel pain.…”
Section: The Pain Sensitivity Questionnairementioning
confidence: 99%
“…Several questionnaires have been developed that measure different aspects of sensitivity, but none to our knowledge focus on widespread physical sensory sensitivity. Some tools focus on only one sensory modality, such as pain (Ruscheweyh et al, 2009(Ruscheweyh et al, , 2012. Other tools, such as the Highly Sensitive Persons Scale (Aron & Aron, 1997a), comparatively place a larger emphasis on emotionality and introversion.…”
Section: Introductionmentioning
confidence: 99%